Zimbabwe's Special Maize Programme for the Import Substitution (Command Agriculture) Scheme: A Hit-and-Miss Affair - Odunze, D.I.; Uwizeyimana, D.E. (Journal of Reviews on Global Economics, 2019)
Increasing food insecurity levels and large import expenditure have been major concerns for the government of Zimbabwe in recent years, leading to the development and implementation of different policies aimed at addressing these issues. In the wake of the devastating drought of 2015, in which only a quarter of the country's annual maize requirement was produced, the Zimbabwean government instituted a targeted command agriculture scheme known in policy terms as the Special Maize Programme for Import Substitution (SMPIS). The programme aimed to increase maize production and to reduce the grain import expenditure of the country. The scheme, although viewed by many as a panacea to the country's increasing food insecurity levels, was equally criticised by many as a drain on the highly depleted financial resources of the country, and arguments have emerged on the merits and demerits of the scheme for the struggling economy. This paper analyses the impact of the SMPIS on maize production and importation in Zimbabwe, as well as the gains and losses of the programme to the Zimbabwean economy.